Community-Based Art Education as a Cultural Transfer Strategy in the Jaran Kepang Art Performance of Semarang Regency - Kusumastuti, Eny; Rohidi, Tjetjep Rohendi; Hartono, Hartono; Cahyono, Agus (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
Jaran Kepang Semarangan is a community based art product. It is a product that has existed in between generations. This research reviews community-based art education as a means to transfer the culture of Jaran Kepang performance. This research is qualitative research with an interdisciplinary approach of sociology to discuss community-based art education and anthropology to dig deeper into the system of knowledge, values, and beliefs within the performance of Jaran Kepang. The research includes a field study in Semarang Regency. The researchers collected the data through observation, interviews, and documentation. The researchers validated the data through triangulation of technique, sources, theory, and times. The data were analysed based on the theories of Janet Adshead along with Miles and Huberman. The research finds that 1) there is a change of community-based art education, including the system of knowledge, values, and beliefs; 2) the transfer of Jaran Kepang is similar to the theory of Cavalli-Sforza and Feldman under the scheme of AGIL (Adaptation, Goal-attainment, Integration, Latent-pattern-maintenance). There is a shift of inheritance system which is from vertical transmission (intergeneration of family) to horizontal transmission or planned regeneration via social media, training, and performance; 3) the development of Jaran Kepang Semarangan is categorized into five types, which are ritualistic ceremony; entertainment of people who hold events, such as marriage, circumcision, gratitude events; rayonan; and entertainment in tourist attraction, cultural festival, or dance competition.